PENGARUH KUALITAS PELAYANAN, GAYA HIDUP DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN PADA PMU ABADI’S BUSANA DI KECAMATAN SILO KABUPATEN JEMBER - Alfaris, Afrizal Mubarok; Hermawan, Haris; Rusdiyanto, Rusdiyanto (Growth, 2024)
In the current era of globalization, competition in the business world is increasingly fierce. This is a demand for every company to be able to maximize its company's performance in order to be able to compete in the market. Currently, many clothing shops have sprung up in Jember Regency, PMU Abadi Clothing is one of them. The competition that occurs requires companies to provide the best for their consumers, for example improving service quality, product quality and lifestyle. This research aims to determine the influence of service quality, lifestyle and product quality on consumer satisfaction at PMU Abadi Clothing in Silo District, Jember Regency. This research uses multiple linear regression analysis methods with the population used to consume PMU Abadi Clothing with a sample size of 96 people. This research shows that service quality, lifestyle and product quality have a positive and significant effect on consumer satisfaction with PMU Abadi Clothing.